Feeding Behavior, Water Intake, and Physiological Parameters of Feedlot Lambs Fed with Diets Containing Babassu Oil Associated with Sunflower Oil Blend - Laryssa V. da Silva; Gleice Kelle S. M. Vilela; Karlyene S. da Rocha; Hactus S. Cavalcanti; Glayciane C. Gois; Francisco Naysson de S. Santos; Fleming S. Campos; Michelle de O. M. Parente; Anderson de M. Zanine; Daniele de J. Ferreira; Tobyas M. de A. Mariz; Danielle de O. Maia; et al. (Veterinary Medicine International)
This study aimed to investigate the impact of dietary inclusion of babassu oil (BO) associated with sunflower oil (SO) on feeding behavior, water intake, and physiological parameters of feedlot lambs. Thirty-five castrated male lambs (16.6 kg ± 3.9 kg) were distributed in a randomized block design with 5 treatments (diets) and 7 replications. The tested diets were oil-free diet (OF), 45 g/kg BO (BO), 30 g/kg BO with an additional 15 g/kg SO (1.5 SO), 22.5 g/kg BO with an additional 22.5 g/kg SO (2.25 SO), and 30 g/kg SO with an additional 15 g/kg BO (3.0 SO) on dry matter (DM) basis. The experimental period lasted 60 days. Animals that received BO diet and the combination of BO with SO had lower intakes of DM and neutral detergent fiber (NDF) compared to the control diet (P<0.05). Differences on the respiratory rate (RR) was observed between animals in the control diet and those in the diets containing SO (P=0.001), with a linear increase in RR as the levels of SO in the diets increased (P=0.004). All physiological parameters showed a time effect (P<0.05). Animals fed with the control diet had higher water intake via drinking fountain (P=0.030) and total water intake (P=0.029) compared to animals fed with diets containing SO. In relation to SO levels, water intake via drinking fountain (P=0.002), total water intake (P=0.002), and total water intake per kg of DM ingested (P=0.001) linearly increased with the levels increase in the composition of the diets. The tested diets did not alter the feeding behavior of the feedlot lambs. However, the combination of BO with different levels of SO reduced DM and water intake via drinking fountain and RR.